2002
DOI: 10.1159/000063692
|View full text |Cite
|
Sign up to set email alerts
|

Topological Properties and Spatial Organization of Villous Capillaries in Normal and Diabetic Placentas

Abstract: Spatial arrangement and complexity of the capillary bed of placental terminal villi were analyzed in 9 normal and 11 diabetic placentas. Specimens were taken by systematic random sampling, fixed and stained in toto, and embedded in paraffin. Fifteen fields of view were sampled systematically from 120-µm-thick sections of specimens and examined using a confocal laser scanning microscope. Series of thin optical sections of terminal villi and their developmental forms were recorded by the confocal microscope and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 97 publications
(72 citation statements)
references
References 12 publications
4
64
0
4
Order By: Relevance
“…Since some of these pregnancies may have included pre-gestational Type 2 diabetes patients, further investigations on gestational diabetes are required to resolve the apparent discrepancies. Recently, a study using three-dimensional visualisation techniques has reported increased longitudinal growth of fetoplacental vessels and enhanced branching angiogenesis in gestational diabetes [49].…”
Section: Discussionmentioning
confidence: 99%
“…Since some of these pregnancies may have included pre-gestational Type 2 diabetes patients, further investigations on gestational diabetes are required to resolve the apparent discrepancies. Recently, a study using three-dimensional visualisation techniques has reported increased longitudinal growth of fetoplacental vessels and enhanced branching angiogenesis in gestational diabetes [49].…”
Section: Discussionmentioning
confidence: 99%
“…These schemes of various forms of villous capillary beds were statistically analyzed, and mean numbers of redundant connections per villus and ratios of villous capillary beds without and with redundant connections were finally summarized in table 1. The results achieved in control placentas were significantly different from results achieved in placentas from pregnancies complicated by both gestational diabetes (Jirkovská et al, 2002) or type 1 diabetes (unpublished data). On the other hand, the results obtained in diabetic groups showed no significant differences.…”
Section: The Branching Of Villous Capillaries In Normal and Diabetic mentioning
confidence: 74%
“…15). The used methods of confocal microscopy and 3D reconstruction enabled us also to demonstrate that placental villous capillaries grow by elongation as well as by sprouting of pre-existing capillaries until term (Jirkovská et al, 1998;Jirkovská et al, 2002, Karen et al, 2003Jirkovská et al, 2008). This finding challenged the hypothesis, expressed by some authors, that placental angiogenesis shifts from the sprouting to the elongating angiogenesis after the 25th week of gestation Mayhew, 2002 b).…”
Section: The Three-dimensional Arrangementmentioning
confidence: 82%
“…For this reason, the evaluation of conventional funicular-Doppler does not have a predictive value in gestational diabetes. However, placentas in this type of pregnancies present hystological alterations, showing a significant decrease of the number of blood vessels [1][2][3] . The search for placental hemodynamic markers may be a good method for the prediction of the metabolic condition of these fetuses, no matter the degree of oxygenation, and for establishing an early prognosis [4][5][6][7] .…”
Section: Introductionmentioning
confidence: 97%